OPTIMIZING THE COACHING TO IMPROVE TEACHERS’ DISCIPLINE IN TEACHING AT SMP NEGERI 2 KUBU BABUSSALAM ROKAN HILIR REGENCY - Baharuddin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was a school action research aiming to improve and enhance the learning process at schools, especially in teachers’ discipline in teaching. The action implemented was optimizing coaching to improve teachers’ discipline in teaching. The subjects in this study consisted of 26 teachers at SMP Negeri 2 Kubu Babussalam. This study was conducted at SMP Negeri 2 Kubu in two cycles. An observation was conducted in cycle I before the treatment, and in cycle II, the observation was conducted after the treatment. Data in this study were collected through observations and coaching treatment. The results showed that the optimization of coaching improved teachers’ discipline and performance in teaching. This could be seen from the percentage of teachers’ discipline after reflection, which was 83%. This percentage increased from the initial data, which was only 58%. The increase in teachers’ activities could also be seen from the observation analysis of teachers’ activities, which obtained a percentage of 85%. This value increased from the initial data, which was only 65%. Therefore, it could be concluded that the application of coaching improved teachers’ discipline in teaching at SMP Negeri 2 Kubu Babussalam Rokan Hilir.